Analisis Status Gizi Anak Balita di Kota Jayapura - Rahayu , Agnes S.; Mendrofa, Hendry K.; Elieser, Elieser; Sidabutar , Astrina R.I.; Andoy , Morris GJ.; Merrandan, Novianto; Salakay , Elisa N.H.; Mahu , Grace F.P.H.; Iswanto, Dais (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
This descriptive study investigates the nutritional status of toddlers at Tanjung Ria Health Center in 2023. It emphasizes the critical importance of proper nutrition during the toddler years, as this period significantly impacts physical, mental, and behavioral development. Factors such as environmental sanitation, parental employment, and education influence nutritional status. The study includes 471 toddlers from Tanjung Ria's Integrated Service Post program. Findings show that most toddlers exhibit normal/good nutritional status, with 51% being male and the majority aged 0-12 months. Anthropometric data reveals 77% normal weight/age, 83% normal height/age, and 79% good weight/height ratios. While most toddlers fare well, a minority exhibit poor or at-risk nutritional status.